2021
DOI: 10.3390/life11090880
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Delayed Doxorubicin-Induced Myocardiotoxicity Associated with Elevation of Cardiac Biomarkers, Depletion of Cellular Antioxidant Enzymes, and Several Histopathological and Ultrastructural Changes

Abstract: Doxorubicin (DOX; Adricin) is an anthracycline antibiotic, which is an efficient anticancer chemotherapeutic agent that targets many types of adult and pediatric tumors, such as breast cancer, leukemia, and lymphomas. However, use of DOX is limited due to its cardiotoxic effects. This study sequentially investigated the mechanistic pathways of the cardiotoxic process of DOX in rats at different post-treatment periods using cumulative dose, which is used in therapeutic regimes. In this regard, 56 male albino ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…These marked drops might be due to increased catabolism because of declined food intake attributed to the noticed loss of appetite and fatigue. This is in agreement with Abdelatty et al ( 2021 ) and Ikewuchi et al ( 2021 ). Increases in serum urea and creatinine, as well as decreased total protein (data not shown), are supportive of the suggested increased catabolism.…”
Section: Discussionsupporting
confidence: 93%
“…These marked drops might be due to increased catabolism because of declined food intake attributed to the noticed loss of appetite and fatigue. This is in agreement with Abdelatty et al ( 2021 ) and Ikewuchi et al ( 2021 ). Increases in serum urea and creatinine, as well as decreased total protein (data not shown), are supportive of the suggested increased catabolism.…”
Section: Discussionsupporting
confidence: 93%
“…This investigation revealed a substantial elevation in all tested cardiac biomarkers; Troponin I, CK- Total, CK-MB, LDH, and AST in DOX-treated group (G2) confirming cardiotoxicity. Our findings were supported by Abdelatty et al . (2021) who reported a substantial elevation in serum cTnT, CK–MB, and AST activities in rats animal post receiving of 2, 4, or 6 mg of DOX/kg bw and increased to their highest level after being exposed to 8 mg/kg bw.…”
Section: Discussionsupporting
confidence: 93%
“…Previous investigations clarified decrease in the antioxidant enzymes level as SOD and CAT accompanied byDOX-induced cardiotoxicity ( Asensio-López et al ., 2017 ; Xiong et al ., 2018 ). And also, a substantial reduction in tissue CAT, GPX, and SOD was observed with DOX medication ( Abdelatty et al ., 2021 ). Moreover, a significant reduction in SOD levels, glutathione (GSH) activity, and increase in lipid peroxide (TBARS) levels were declared in rats treated with DOX ( Abdel-Raheem and Abdel-Ghany, 2009 ).…”
Section: Discussionmentioning
confidence: 97%
“…The liver is the primary organ concerned with the biotransformation of chemicals, which mostly results in markedly detrimental effects on the biochemistry of hepatocytes, such as excessive ROS generation, which causes oxidative damage not only in the liver but also in other organs, including the kidneys, spleen, and hematopoietic system (36,(43)(44)(45)(46)(47)(48)(49)(50). In this study, Bz-treated rats revealed significant increases in serum bioactivities of AST, ALT, ALP, and LDH and decreased serum total protein, albumin, and α2-and γ-globulin concentrations.…”
Section: Discussionmentioning
confidence: 99%